2009
DOI: 10.1042/bj20081505
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-targeted synergistic activity of docosahexaenoic acid and lysozyme against Pseudomonas aeruginosa

Abstract: SYNOPSIS Antimicrobial polypeptides including lysozymes (Ly) have membrane perturbing activity and are well documented effector molecules of innate immunity. In cystic fibrosis, a hereditary disease with frequent lung infection with Pseudomonas aeruginosa, the free fatty acid docosahexaenoic acid (DA), but not oleic acid (OA), is decreased and DA supplementation has been shown to improve the clinical condition in these patients. We hypothesized that DA may alone, or in conjunction with Ly, exert antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…Indeed, synergistic interactions between antimicrobial lipids and proteins for intrinsic host defense have been demonstrated in some reports. 18,26,36 A review of the normal ocular microbiota shows that numbers of microorganisms that can be isolated from tears (<100 CFU/lL) are strikingly less than those isolated from saliva (10 7 -10 8 CFU/lL). 37 Although these secretions have similar antimicrobial proteins for innate defense, the apparent difference in the microbial load may be attributed to the lipid quantities that the two secretions contain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, synergistic interactions between antimicrobial lipids and proteins for intrinsic host defense have been demonstrated in some reports. 18,26,36 A review of the normal ocular microbiota shows that numbers of microorganisms that can be isolated from tears (<100 CFU/lL) are strikingly less than those isolated from saliva (10 7 -10 8 CFU/lL). 37 Although these secretions have similar antimicrobial proteins for innate defense, the apparent difference in the microbial load may be attributed to the lipid quantities that the two secretions contain.…”
Section: Discussionmentioning
confidence: 99%
“…In the human colon, the concentration of shorter-chain FA have been measured in the millimolar range (e.g., 124 mM ;Bergman 1990) and that has been shown to inhibit the growth of bacteria such as E. coli O157:H7 . Although the effects of inhibitory FA and monoglycerides on bacterial growth are additive (Sun et al 2003), many FA have synergistic effects against pathogens with other elements of the innate immune system, including antimicrobial peptides (Nakatsuji et al 2010), lactoferrin and lysozyme (Ellison and Giehl 1991;Martinez et al 2009), andgastric acid (Bergsson et al 2002;Thormar et al 2006). The amplification of antipathogen activity by host factors suggests that some FA, even at concentrations in which they are inactive in isolation, may have the ability to modify the gut microbiota in vivo and thus alter infectious risk.…”
Section: Discussionmentioning
confidence: 99%
“…Tollin et al [38] reported synergistic activity between vernix caseosa lipids and the antimicrobial peptide LL37 whereby this effect was attributed to FFA in vernix. We found synergistic effects between nasal fluid lipid extracts and the antimicrobial peptide human neutrophil peptide HNP1 [53] , and between the free fatty acid docosahexaenoic acid and lysozyme [67] . The latter study demonstrated that in the presence of lysozyme, docosahexaenoic acid accumulates in the bacterial cell membrane.…”
Section: Synergism With Ampsmentioning
confidence: 93%